2004
DOI: 10.1007/s00294-003-0449-5
|View full text |Cite
|
Sign up to set email alerts
|

KNQ1 , a Kluyveromyces lactis gene encoding a drug efflux permease

Abstract: Several transport systems play an important role in conferring multiple drug resistance, presumably due to their catalysis of the energy-dependent extrusion of a large number of structurally and functionally unrelated compounds out of the cells. In the present work, the gene named KNQ1 (encoding Kluyveromyces lactis membrane permease) was cloned by functional complementation of the cycloheximide-hypersensitivity phenotype of the Saccharomyces cerevisiae mutant strain lacking a functional PDR5 gene. The isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…The authors discussed the accumulation of diVerent carotenoid precursors as a possible reason for the diVerent eVects; however, this was by no means the only possible explanation because amitrole shows a number of additional eVects in microorganisms, plants, and animals. It is known to inactivate monofunctional catalases (Shima et al 1999;Ghadermarzi et al 1999;Switala et al 2002) leading to increased levels of H 2 O 2 (Morita et al 1999) and free radicals (Dikalova et al 2001) which in turn can stimulate phosphorylation of mitogen-activated protein kinases (Srivastava et al 2000) and induce apoptosis (Lavrentiadou et al 2001); its mutagenic potency has been reported (Hatch et al 2001;Fluckiger-Isler et al 2004); its cytotoxicity has been used for resistance studies (Morissey et al 1999;Takacova et al 2004); as a histidine analog, it can induce amino acid starvation, used as a tool to study gene activation responsible for general amino acid control (Tripathi et al 2002;Takaku et al 2004;Yin et al 2004). Inhibition of the hydrogenation of geranylgeraniol to phytol by amitrole in seedlings transferred from darkness to light (Rüdiger et al 1976;Rüdiger and Benz 1979) is probably caused by inhibition of de novo synthesis of geranylgeranyl reductase because the same eVect was also observed by treatment with cycloheximide (Rassadina et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…The authors discussed the accumulation of diVerent carotenoid precursors as a possible reason for the diVerent eVects; however, this was by no means the only possible explanation because amitrole shows a number of additional eVects in microorganisms, plants, and animals. It is known to inactivate monofunctional catalases (Shima et al 1999;Ghadermarzi et al 1999;Switala et al 2002) leading to increased levels of H 2 O 2 (Morita et al 1999) and free radicals (Dikalova et al 2001) which in turn can stimulate phosphorylation of mitogen-activated protein kinases (Srivastava et al 2000) and induce apoptosis (Lavrentiadou et al 2001); its mutagenic potency has been reported (Hatch et al 2001;Fluckiger-Isler et al 2004); its cytotoxicity has been used for resistance studies (Morissey et al 1999;Takacova et al 2004); as a histidine analog, it can induce amino acid starvation, used as a tool to study gene activation responsible for general amino acid control (Tripathi et al 2002;Takaku et al 2004;Yin et al 2004). Inhibition of the hydrogenation of geranylgeraniol to phytol by amitrole in seedlings transferred from darkness to light (Rüdiger et al 1976;Rüdiger and Benz 1979) is probably caused by inhibition of de novo synthesis of geranylgeranyl reductase because the same eVect was also observed by treatment with cycloheximide (Rassadina et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Among these, fragments 33 and 46 did not yield any database hits. The amino acid sequence corresponding to fragment 34 showed similarity with the KNQ1 protein identified in K. lactis (42). This is a drug-efflux permease possibly responsible for decreasing concentrations of several toxic compounds in the cytoplasm of yeast cells.…”
Section: Resultsmentioning
confidence: 92%
“…Indeed, KlYap1p contributed to the KNQ1 gene regulation in response to boron exposure since its expression was strongly diminished in Klyap1Δ cells. Previous studies have shown that KNQ1 expression was upregulated in response to hydrogen peroxide, tert-butyl-hydroperoxide, dithiothreitol, and NaAsO 2 , As(III); so, it seems that K. lactis regulates stress-responsive genes and adjusts processes related to redox processes and transport in response to various stresses (Takacova et al 2004;Marchi et al 2007;Veide Vilg et al 2014). On the other hand, ScATR1 overexpression provided resistance to boric acid, salt stress but not to oxidative, heavy metal, or acetic stress (Kaya et al 2009).…”
Section: Discussionmentioning
confidence: 94%
“…The K. lactis KNQ1 gene encodes a protein belonging to the DHA2-MFS superfamily with a putative role in multidrug resistance (Takacova et al 2004;Gbelska et al 2006). Although the phylogenetic analysis has shown that the Knq1p defines new branch in a phylogenetic tree, its closest homologues in S. cerevisiae are the products of paralogs ScATR1 and YMR279c, both with the recently identified role in boron transport (Kaya et al 2009;Bozdag et al 2011;Dias and Sá-Correia 2013).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation